The taxation of ‘intangible’ innovation: the Patent Box in Europe and the Italian case - Caramia, Lucrezia Valentina (Review of European and Comparative Law, 2022)
“Patent Box” is a term for the application of a lower corporate tax rate to the income derived from the ownership of patents. This tax subsidy instrument has been introduced in several countries since 2000. This paper, through a comparative analysis, compares the Patent Box adopted in three different European jurisdictions, which are distinguished by the particular attractiveness of their tax systems, and then focuses on the peculiar case of the Italian Patent Box. Art. 6, D.L. of 21 October 2021, n. 146, in fact, introduces the new discipline of the Patent Box, a preferential taxation mechanism of income from the direct and indirect use of certain intangible assets which, only two months later, has already undergone further and important changes by art. 1, comma 10, of L. 30 December 2021, n. 234: this disruption requires considering the causes of the legislative intervention and, therefore, the structure of a tax promotion mechanism that has already received relevant consideration in the OECD.